Elite Minds: A Serious Game for Assessing Cognitive Abilities in Police Special Forces Recruitment - Muhly, Fabian; Leo, Philipp; Dössegger, Alain (International Journal of Police Science, 2025)
Police special forces perform both physically and mentally demanding, invaluable tasks in combatting terrorism, organized crime and in hostage situations. To guarantee mission success, it is detrimental to have the personnel that is able to match physical and cognitive requirements of the job. Whereas physical abilities can be assessed objectively, assessment tools that uncover cognitive abilities such as, amongst others, teamwork, success orientation, logical reasoning, or problem solving often do not reveal the real abilities of the candidate. We proposed an interactive tabletop serious game to the special forces of a Swiss cantonal police for the evaluation of its potential as assessment tool of cognitive abilities in the recruitment process. In a test run with operators and assessors of the corps, the assessors evaluated its suitability and were able to observe seven out of nine desired cognitive competency dimensions. Consequently, the special forces division of the respective cantonal police is highly likely implementing the serious game as an assessment tool in the regular recruitment process in the future. By doing so, they intend to more accurately assess cognitive abilities of applicants to select the right personnel for this demanding employment.